Long-term outcomes of Aripiprazole long-acting injectable: a 10-year mirror image study of patient acceptability and treatment effectiveness - Joshua Barnett; Sofia Pappa (Schizophrenia, 2025)
Abstract Relapses are frequent in schizophrenia and other psychotic disorders. While long-acting injectable antipsychotics (LAIs) are effective in preventing hospital admissions and improving adherence and patient outcomes, they are still under-utilised. Furthermore, evidence from newer formulations and longitudinal studies, despite their commonly long-term use, remains limited. To address this scarcity of data, this study aims to evaluate the long-term effectiveness and acceptability of once-monthly Aripiprazole long-acting injectable (ALAI), the only third-generation antipsychotic available in long-acting formulation. In this pragmatic, independent, ten-year mirror-image study conducted within a large urban mental health service in London, UK, we assessed hospital admission rates and treatment retention over 5 years following ALAI initiation in a naturalistic adult cohort. Frequency and length of hospitalisations in the 5 years pre- and post-initiation were recorded using electronic records, as were discontinuation rates and reasons. Separate analyses were performed comparing outcomes between treatment completers and discontinuers, as well as between those with schizophrenia vs other diagnoses. In total, 135 patients were included in the study (63% with Schizophrenia, 37% with other diagnoses). The discontinuation rate was 47% at 5 years (23.7%, 13.6%, 7.9%, 7.3% and 5.3% in years 1 to 5 respectively). Among the 53% who completed 5 years of ALAI treatment, we observed an 88.5% reduction in mean number (1.57 to 0.18, p < 0.001) and a 90% reduction in mean length of hospitalizations compared to 5 years pre-ALAI initiation (103 to 10 days, p < 0.0001). Median admissions and length fell from 1 to 0 and 68 to 0 days (p < 0.001), respectively. In contrast, discontinuers (47%) exhibited inferior outcomes and showed only a 29.9% reduction in admissions over 5 years. Patients were more likely to discontinue due to poor compliance and ineffectiveness and rarely due to tolerability issues. Apart from switching to ALAI from another LAI, there were no major clinical or demographic predictors of treatment continuation. Outcomes were consistent independent of diagnosis. Potential confounders however must not be overlooked, such as the exclusion of a large number of patients due to strict eligibility criteria as well as changes to healthcare policy over the study period. This is the first study to report 5-year hospitalisation and treatment persistence outcomes with ALAI. Its sustained use was associated with substantial reductions in hospital use, with 85% of completers requiring no further admissions, compared to 30% of discontinuers. These real-world findings support the long-term value of ALAI and may help address common barriers to LAI adoption in clinical decision-making.